CASE STUDY ABOUT LOW MOTIVATION TO LEARN SBDP IN CLASS V STUDENTS OF AL-KHAIRAT SOLONSA SD IN THE PANDEMIC TIME COVID 19 - Sulviana Sulviana; Yun Ratna Lagandesa (Universitas Tadulako, 2021)
The focus of this research is the Low SBdP Learning Motivation in Class V SD Al-Khairat Solonsa during the Covid 19 Pandemic. This study aims to determine the factors causing the low SBdP Learning Motivation in Class V SD Al-Khairat Solonsa Students during the Covid Pandemic. 19. The subjects of this study were 19 grade students of SD Al-Khairat Solonsa. Data collection techniques in this study using observation, questionnaires, interviews and documentation with the technique